2016
DOI: 10.1902/jop.2015.150161
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Local Delivery of Aloe Vera Gel in Patients With Type 2 Diabetes and Chronic Periodontitis: A Randomized, Controlled Clinical Trial

Abstract: Adjunctive use of locally delivered AV gel, in comparison to locally delivered placebo gel, is associated with greater reduction in PI, mSBI, and PD as well as more gain in CAL in patients with T2DM and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 35 publications
1
35
0
2
Order By: Relevance
“…In another study by Pradeep et al. on adjunctive local delivery of AV gel in type II diabetics with chronic periodontitis, an improvement in clinical parameters was demonstrated . These results are also consistent with our present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In another study by Pradeep et al. on adjunctive local delivery of AV gel in type II diabetics with chronic periodontitis, an improvement in clinical parameters was demonstrated . These results are also consistent with our present study.…”
Section: Discussionsupporting
confidence: 93%
“…After intensive in vitro investigations for optimization and stability, the MtF gel and AV gel were prepared at the Government College of Pharmacy, Bengaluru, India, following the documented procedures …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Aloe vera (AV) AV is a herbal product with antioxidant, anti-inflammatory, antimicrobial, healing-promoting, and immune-boosting properties. In a study by Pradeep et al, [29] AV gel used as an adjunct to SRP in the treatment of patients with Type 2 diabetes mellitus and CP, showed significantly greater improvement in clinical parameter compared to placebo group.…”
Section: Probioticsmentioning
confidence: 97%
“…An Indian group found that adjunctive use of locally delivered AVG, in comparison to locally delivered placebo gel, was associated with greater reduction in plaque index, modified sulcus bleeding index, and probing depth as well as more gain in clinical attachment level in patients with Type 2 diabetes mellitus and chronic periodontitis. 37 In an interesting in vitro study, a cytotoxicity assay showed that Aloe vera in prearranged concentrations was cell-compatible and indicated a dose-dependent antiviral effect of Aloe vera. 38 The inhibitory effect of various concentrations of Aloe vera was observed 1 h after the Vero cell was infected with herpes simplex virus 1 (HSV-1).…”
Section: Clinical Studiesmentioning
confidence: 99%